ANALYZING THE STRATEGIC ALIGNMENT BETWEEN INFORMATION SYSTEM TECHNOLOGY AND BUSINESS PROCESS IN SMALL MEDIUM ENTERPRISE (SME) USING FRAMEWORK COBIT 4.1– A CASE STUDY IN UNIVERSAL TRADING, SURABAYA - Benih Hartanti (TIJAB (The International Journal of Applied Business), 2017)
This research was conducted in Universal Trading as one of SME that applies Information Technology as daily business process in order to analyze whether the use of Information Technology is alligned with the strategy formulation. Type of research is Descriptive Research with Qualitative technique by using direct observation and depth interview with all user of TI from leader to staff. In depicting a further detail description, Internal and External Matrixas well as COBIT Verse 4.1 were utilized in supporting so. From the position of Average as a result of IFE-EFE Matrix and the Score of COBIT 4.1 in primary process of Strategic Allingment is 2,95 could be concluded that only strategy of new market penetration could be alligned by the use of Information Technology as the company basic business process is limiting the strategy of new product development using only company’s internal source. Keyword: strategic allignment, information technology, COBIT 4.1